From constructive engagement to renewed estrangement? Securitization and Turkey's deteriorating relations with its Kurdish minority. (1st October 2016) - Weiss, Matthew
ABSTRACT: Over the last several years, the political will of the governing AKP in Turkey to make the historic compromises necessary to complete the peace process with the Kurds has sharply declined. This paper will examine the causes of the breakdown in the Turkish-Kurdish peace process and the Turkish government's lurch in a nationalist direction in its approach towards the Kurdish minority from the standpoint of 'securitization' theory. The key catalysts, it is argued, for the re-emergence of a securitization paradigm in Turkey's handling of the Kurdish issue are: (1) Turkey's stalled bid for accession to the European Union; (2) the intensifying electoral competition between AKP and the Kurdish movement parties, coupled with the instrumentalization of the Kurdish peace process to serve President Recep Tayyip Erdoğan's quest to install a dominant presidential system and (3) the spillover effects of Syria's civil war on Turkey's relations with its own Kurdish populace.